Pengembangan DSP Labuan Bajo: Sebuah Quantum Leap - Syafera, Arkan (Pusat Studi Pariwisata Universitas Gadjah Mada, 2024)
The acceleration in the development of DSP (Super Priority Destinations) in Labuan Bajo has apparently meant that many tourism actors need to push the limits of their potential to keep up with the acceleration that is already underway. The process of learning about the world of tourism takes a long time, but development continues to be massive even though the tourism foundation there is not yet very strong, that was a problem. To explore this, this research has two main questions: a) how is Labuan Bajo tourism accelerated?; and b) how do tourism actors react to the acceleration of Labuan Bajo tourism? Data was searched using literature study methods, participant observation and in-depth interviews. As a result, Labuan Bajo's tourism quantum leap is not based on internal population growth, but instead exists to stimulate population growth, in this case tourists.